A headache presenting in the emergency room, a clinical manifestation of an unfortunate diagnosis (grade III left frontal anaplastic ependymoma with 1p deletion). (2nd August 2013) - Flores-Robles, B J; Hurtarte-Sandoval, A R; Harrison, R M; Cuevas, C C
Abstract : An 18-year-old girl presented with a headache and behavioural changes. She was found to have a frontal mass. Neuroimaging revealed an intra-axial mass, located at the left frontal cortical/subcortical region approximately 6×7, 5×7, 5 cm (TxApxL), having a heterogeneous density with cysts and calcification. She had total gross excision of the neoplasm. Histopathological examination revealed an anaplastic ependymoma. Fluorescence in situ hybridisation, a molecular cytogenetic test, reported deletion of 1p without deletion of 19q. The patient had a good postoperative improvement.